Study of the distribution of health services in the public-sector hospitals in the Syrian Arab Republic and the role of rehabilitation and training in raising the level of health services. (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The aim of this study is to identify the quality of health services provided in the public sector hospitals in the Syrian Arab Republic. The paper adopts the analytical descriptive approach where the phenomenon or the problem under study is described accurately and expressed quantitatively and qualitatively. The comparison method is used to identify the similarities and differences between the Syrian governorates. The secondary data, available in the local Health Directorate and the Central Library of Statistics, are reviewed. Some of them are selected to present comparisons, in addition to reference to several secondary sources, such as studies and reports related to the study, to evaluate the quality of the provided health services. After analyzing the data, we found that Syria did succeed in improving the health conditions of citizens through the study of statistical indicators related to health. Pertaining to training, it shows the lack of the required level of quality of the offered health services in hospitals at the time that training, especially in this sector to keep abreast of successive global developments and successive which have great impact on the health services quality.